2015
DOI: 10.1016/j.neuroimage.2015.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Validated automatic brain extraction of head CT images

Abstract: Background X-ray Computed Tomography (CT) imaging of the brain is commonly used in diagnostic settings. Although CT scans are primarily used in clinical practice, they are increasingly used in research. A fundamental processing step in brain imaging research is brain extraction – the process of separating the brain tissue from all other tissues. Methods for brain extraction have either been 1) validated but not fully automated, or 2) fully automated and informally proposed, but never formally validated. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 22 publications
1
57
0
Order By: Relevance
“…ICV was calculated automatically using FSL (Analysis Group, FMRIB, Oxford, UK) 21 . In those cases where the automatic technique failed to extract the entire cranial vault, a semiautomatic approach using Simpleware ScanIP (Simpleware Ltd., Exeter, UK) was adopted.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…ICV was calculated automatically using FSL (Analysis Group, FMRIB, Oxford, UK) 21 . In those cases where the automatic technique failed to extract the entire cranial vault, a semiautomatic approach using Simpleware ScanIP (Simpleware Ltd., Exeter, UK) was adopted.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…This outcome was expected because the MR imaging-based default tissue probabilistic atlas map (TPM; https://www.fil.ion.ucl.ac.uk/spm/toolbox/TPM/) that we used did not model some of the anatomy present in CT images, and binarizing the masks by thresholding mitigated these errors. Additionally, the systematic bias in the TIV estimate using the binary masks was better than TIV estimated using the BET-based method by Muschelli et al 13 The utility of CTSeg was demonstrated in a cross-sectional dataset containing AD and control groups. We found that CTSeg-estimated volumes had a significant %TBV (P , .05) difference between the AD and control groups in a linear regression model with age, sex, and AD diagnosis as covariates.…”
Section: Discussionmentioning
confidence: 94%
“…24 The TIV estimates of CTSeg were also compared with the state-of-the-art FSL Brain Extraction Tool for CT (BET; http://bit.ly/CTBET_BASH). 13 CTSeg-estimated volumes from the images of age-matched subjects with AD and controls were used to compare brain atrophy between patients with AD and controls. Subjects with AD and controls were age-matched by minimizing the age difference using the MatchIt package 25 in R (https://www.rdocumentation.org/ packages/MatchIt/versions/3.0.2/topics/matchit).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain extraction is a six-step process, which was implemented using the Insight Segmentation and Registration Toolkit (ITK, https://itk.org/). The framework used for this follows the approach described by Muschelli et al 20 , but was implemented in a slice-by-slice fashion. Therefore, each slice of the scan is first smoothed using a Gaussian filter (variance = 4 pixels), intensity thresholded between 0 and 100 HU, and then eroded using a circular structuring element (radius = 1 pixel).…”
Section: Methodsmentioning
confidence: 99%